Hardenable composition for dental restorations

A curable dental composition using specific (meth)acrylic acid ester and mono(meth)acrylic acid ester compounds with a polymerization initiator addresses operability and strength issues, achieving high mechanical strength, water resistance, and polishability for dental restorations and mill blanks.

JP7611819B2Active Publication Date: 2025-01-10KURARAY NORITAKE DENTAL
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021516214
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-24
Filing Date
2020-04-23
Publication Date
2025-01-10
Estimated Expiration
2040-04-23

AI Technical Summary

Technical Problem

Existing dental composite resins and mill blanks face issues with poor operability, mechanical strength, and water resistance, particularly when fine particles are blended to enhance abrasiveness, leading to high viscosity and sticky compositions that hinder effective use with dental instruments.

Method used

A curable composition comprising (meth)acrylic acid ester compounds with multiple (meth)acryloyloxy groups, mono(meth)acrylic acid ester compounds with specific average primary particle sizes, and a polymerization initiator, which together provide high mechanical strength, water resistance, and polishability, while maintaining low viscosity for improved operability.

Benefits of technology

The composition achieves high mechanical strength, excellent water resistance, and polishability, with suppressed bubble formation, and enhanced operability, making it suitable for dental restorations and mill blanks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611819000001
    Figure 0007611819000001
  • Figure 0007611819000002
    Figure 0007611819000002
  • Figure 0007611819000003
    Figure 0007611819000003
Patent Text Reader

Abstract

The present invention provides a curable composition for dental restoration, a cured product of which has high mechanical strength and excellent water resistance and polishability; a dental composite resin comprising the curable composition for dental restoration; and a dental mill blank comprising a cured product of the curable composition for dental restoration. The present invention relates to a curable composition for dental restoration that contains a (meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups per molecule, a mono(meth)acrylic acid ester compound (B), an inorganic filler (C) having an average primary particle size of 0.01-5 μm, and a polymerization initiator (D). The mono(meth)acrylic acid ester compound includes at least one selected from the group consisting of mono(meth)acrylic acid ester compounds (B-1) represented by general formula (I) and mono(meth)acrylic acid ester compounds (B)-2) represented by general formula (II).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dental material capable of partially or entirely replacing natural teeth in the field of dentistry, in particular to a hardenable composition for dental restorations that is suitably used as a dental composite resin, and to a dental mill blank comprising a hardened product of the hardenable composition for dental restorations. [Background technology]

[0002] A dental restorative hardenable composition consisting of a polymerizable monomer, a filler, and a polymerization initiator is called a dental composite resin, and is the most widely used dental material today for repairing missing teeth and caries. The dental composite resin is required to have sufficient mechanical strength to replace natural teeth in the hardened product after polymerization and hardening, water resistance to withstand long-term intraoral restoration, and polishability to obtain a luster equivalent to that of natural teeth, and in the paste state before polymerization and hardening, it is required to have operability suitable for filling cavities using dental instruments, etc.

[0003] On the other hand, dental mill blanks are materials used to manufacture dental prostheses such as inlays and crowns using a CAD / CAM system, which is designed by computer and cut by a milling device, and the demand for them has been rapidly increasing in recent years. Blocks of suitable sizes such as rectangular parallelepipeds, cylinders, and disks are supplied as dental mill blanks, which are set in a cutting machine and cut out to obtain restorations in the shape of a crown or dentition. Various materials have been proposed as materials for dental mill blanks, including glass ceramics, zirconia, titanium, acrylic resins, and composite materials containing polymer resins and inorganic fillers. Dental mill blanks are also required to have sufficient mechanical strength to replace natural teeth, water resistance to withstand long-term intraoral restorations, and polishability to obtain the same luster as natural teeth. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-126417 A [Patent Document 2] JP 2016-8211 A [Patent Document 3] International Publication No. 2014 / 021343 Summary of the Invention [Problem to be solved by the invention]

[0005] In order to realize excellent paste operability and high curing properties, a technique has been proposed in which a mixture of (meth)acrylic acid ester compounds having two or more (meth)acryloyloxy groups and aromatic rings in one molecule is combined with a hydroxyl group-containing compound and a hydroxyl group-free compound (Patent Document 1). However, as a result of the inventors' investigation, when fine particles were blended to realize polishing properties, the paste had poor operability, and there were problems in that the mechanical strength and water resistance were low.

[0006] Also, in order to realize excellent paste operability and high mechanical strength and polishability after hardening, a technique of combining a mono(meth)acrylamide compound with a (meth)acrylic acid ester compound has been proposed (Patent Document 2). However, as a result of the inventors' investigation, this technique had the problem of low mechanical strength and low water resistance.

[0007] As an example of a dental mill blank, a method for producing a dental mill blank has been described in which, in order to achieve mechanical strength and abrasiveness, an inorganic filler is press-molded to obtain a molded body, and then the molded body is immersed in a polymerizable monomer and polymerized by heating (Patent Document 3). This manufacturing method makes it possible to densely pack nanoparticles, and a dental mill blank with excellent mechanical strength and abrasiveness can be obtained. However, as a result of the studies by the present inventors, when a polymerizable monomer that exhibits high mechanical strength after curing is used to achieve high mechanical strength, there is a problem that the viscosity of the polymerizable monomer is high and it does not penetrate into the molded body. In addition, there is no mention of water resistance, leaving room for improvement.

[0008] The present invention has been made to solve the above problems of the prior art, and aims to provide a dental restorative hardenable composition having high mechanical strength and excellent water resistance and abrasion resistance when cured, a dental composite resin made of the dental restorative hardenable composition, and a dental mill blank made of the hardened product of the dental restorative hardenable composition. Another object of the present invention is to provide a dental restorative hardenable composition having excellent paste operability and a dental composite resin made of the dental restorative hardenable composition. Another object of the present invention is to provide a dental mill blank that can suppress bubbles generated in the hardened product and has excellent appearance. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted intensive research to achieve the above-mentioned object, and as a result have surprisingly found that a dental restorative hardenable composition containing a (meth)acrylic acid ester compound having two or more (meth)acryloyloxy groups in one molecule, a specific mono(meth)acrylic acid ester compound, an inorganic filler having an average primary particle size of 0.01 to 5 μm, and a polymerization initiator can be obtained, which results in a hardened product having high mechanical strength, water resistance and polishing property, and which has excellent paste properties before hardening. Based on this finding, the present inventors conducted further research and completed the present invention.

[0010] That is, the present invention includes the following inventions. [1] A method for producing a polymerizable composition comprising: a (meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups in one molecule; a mono(meth)acrylic acid ester compound (B); an inorganic filler (C) having an average primary particle size of 0.01 to 5 μm; and a polymerization initiator (D); the mono(meth)acrylic acid ester compound (B) is a mono(meth)acrylic acid ester compound (B-1) represented by the following general formula (I) and a mono(meth)acrylic acid ester compound (B-2) represented by the following general formula (II): [ka] [ka] [In the formula, R 1 and R 2 are each independently a group represented by the following general formula (i) or a group represented by the following general formula (ii), and X is a divalent hydrocarbon group having 1 to 6 carbon atoms or an oxygen atom. [ka] [ka] (In the formula, R 3 and R 5 are each independently a divalent hydrocarbon group having 1 to 10 carbon atoms, R 4 and R 6 each independently represents a hydrogen atom or a methyl group, and k and l each independently represent an integer of 0 to 6.)] A hardenable composition for dental restoration, comprising at least one member selected from the group consisting of: [2] The hardenable composition for dental restorations according to [1], wherein the content of the inorganic filler (C) is 50 to 95 mass % based on the total amount of the hardenable composition for dental restorations. [3] The dental restorative hardenable composition according to [1] or [2], wherein the mono(meth)acrylic acid ester compound (B) contains a mono(meth)acrylic acid ester compound (B-2) represented by general formula (II): [4] The hardenable composition for dental restoration according to [3], wherein X is an oxygen atom. [5] The hardenable composition for dental restoration according to any one of [1] to [4], wherein k and l are 0 or 1. [6] The hardenable composition for dental restoration according to any one of [1] to [5], wherein the (meth)acrylic acid ester compound (A) contains a compound having a cyclic structure. [7] The hardenable composition for dental restoration according to [6], wherein the compound having a cyclic structure is a compound (A-1) having an aromatic ring. [8] The hardenable composition for dental restoration according to [7], wherein the compound (A-1) having an aromatic ring is a compound having a bisphenol A skeleton. [9] The hardenable composition for dental restoration according to any one of [1] to [8], wherein the (meth)acrylic acid ester compound (A) comprises a compound having no hydroxy group, carboxy group, primary amino group, secondary amino group, amide group, urea bond, or urethane bond.

[10] The hardenable composition for dental restoration according to any one of [1] to [9], which has a nitrogen-containing heterocycle and is substantially free of a compound having a polymerizable functional group.

[11] The hardenable composition for dental restoration according to any one of [1] to

[10] , wherein the polymerization initiator (D) contains a photopolymerization initiator.

[12] The hardenable composition for dental restoration according to any one of [1] to

[11] , wherein the polymerization initiator (D) contains a thermal polymerization initiator.

[13] The hardenable composition for dental restoration according to any one of [1] to

[12] , further comprising a polymer.

[14] The hardenable composition for dental restorations described in

[13] , wherein the polymer is a prepolymer having unreacted polymerizable functional groups.

[15] The hardenable composition for dental restoration according to

[14] , wherein the number of unreacted polymerizable functional groups per molecule of the prepolymer is 5 to 1,000.

[16] The hardenable composition for dental restorations according to

[14] or

[15] , wherein the prepolymer has a weight average molecular weight of 1,000 or more and 1,000,000 or less.

[17] A dental composite resin comprising the hardenable composition for dental restoration according to any one of [1] to

[16] .

[18] A dental mill blank comprising the dental restorative hardenable composition according to any one of [1] to

[16] . Effect of the Invention

[0011] The dental restorative hardenable composition of the present invention has high mechanical strength and excellent water resistance and abrasion resistance after curing. The dental restorative hardenable composition of the present invention also has excellent paste operability. Furthermore, the dental restorative hardenable composition of the present invention can suppress bubbles from being generated in the cured product, and has excellent appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The dental restorative hardenable composition of the present invention contains a (meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups in one molecule, a mono(meth)acrylic acid ester compound (B), an inorganic filler (C) having an average primary particle size of 0.01 to 5 μm, and a polymerization initiator (D). It is important that the mono(meth)acrylic acid ester compound (B) contains at least one selected from the group consisting of the mono(meth)acrylic acid ester compound (B-1) represented by the above general formula (I) and the mono(meth)acrylic acid ester compound (B-2) represented by the above general formula (II).

[0013] The reason why the above-mentioned constitution provides the effect of the present invention is not necessarily clear, but the present inventors speculate as follows. It is known that fine particles are blended to realize the polishing property required for dental materials, but the dental restorative hardenable composition obtained by mixing the fine particles with a polymerizable monomer has a problem of high viscosity and stickiness, that is, when filling a cavity with a dental instrument, the dental restorative hardenable composition adheres to the instrument, resulting in poor operability. On the other hand, a low-viscosity polymerizable monomer is sometimes used to improve operability, but the mechanical strength of the obtained hardened product tends to be low. By using a mono(meth)acrylic acid ester compound (B) containing at least one selected from the group consisting of a mono(meth)acrylic acid ester compound (B-1) represented by the above general formula (I) and a mono(meth)acrylic acid ester compound (B-2) represented by the above general formula (II), the viscosity can be kept low, and the operability of the obtained dental restorative hardenable composition is improved, while the hardened product exhibits high mechanical strength. It is presumed that the reason for the improvement in mechanical strength is that the π-π interaction of the aromatic rings contained in the mono(meth)acrylic acid ester compound (B) strengthens the interaction between the polymer chains after polymerization, improving the mechanical strength of the cured product. In addition, the use of the mono(meth)acrylic acid ester compound (B) can keep the viscosity low, and the generation of bubbles in the cured product can be suppressed.

[0014] The present invention will be described in detail below. In this specification, the upper and lower limit values ​​of the numerical ranges (contents of each component, values ​​calculated from each component, and each physical property, etc.) can be appropriately combined. In this specification, the numerical values ​​of each symbol in the formula can also be appropriately combined.

[0015] [(Meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups in one molecule] The (meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups in one molecule is used in the dental restorative hardening composition of the present invention to impart water resistance and mechanical strength to the hardened product of the dental restorative hardening composition. The (meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups in one molecule in the present invention (hereinafter, sometimes referred to as "(meth)acrylic acid ester compound (A)") is not particularly limited as long as it exhibits the effects of the present invention and is a known (meth)acrylic acid ester compound used in dental composite resins, etc., but it is preferable to include a compound having a cyclic structure, which is a rigid skeleton, in order to improve the mechanical strength after hardening. Examples of the compound having a cyclic structure include a compound (A-1) having an aromatic ring, a compound (A-2) having an alicyclic ring, and a compound (A-3) having a heterocyclic ring. The (meth)acrylic acid ester compound (A) (for example, the compound (A-1) having an aromatic ring, the compound (A-2) having an alicyclic ring, and the compound (A-3) having a heterocyclic ring) may be a polyfunctional polymerizable compound having one or more other polymerizable functional groups other than two or more (meth)acryloyloxy groups, as long as it has two or more (meth)acryloyloxy groups in one molecule, or may be a bifunctional polymerizable compound having only two (meth)acryloyloxy groups in one molecule. In the present invention, the (meth)acryloyloxy group and the other polymerizable functional groups are collectively referred to as "polymerizable functional groups". Examples of the polymerizable functional groups possessed by the (meth)acrylic acid ester compound (A) include those similar to those of the prepolymer described below, and a (meth)acryloyl group is preferable, and a (meth)acryloyloxy group is more preferable. Hereinafter, for example, the compound (A-3) having a heterocyclic ring is also referred to as "a compound (A-3) having a heterocyclic ring and a polymerizable functional group". In one preferred embodiment, the (meth)acrylic acid ester compound (A) has only a (meth)acryloyloxy group as a polymerizable functional group, and in another preferred embodiment, the compound (A-1) having an aromatic ring or the compound (A-2) having an alicyclic ring has only a (meth)acryloyloxy group as a polymerizable functional group.

[0016] Furthermore, in terms of being able to improve the mechanical strength after curing by π-π interaction with the mono(meth)acrylic acid ester compound (B) described later, the (meth)acrylic acid ester compound (A) preferably contains a compound (A-1) having an aromatic ring, and more preferably contains a compound having a bisphenol A skeleton. In the present invention, the term "(meth)acrylic" is used to mean both methacryl and acrylic. The same applies to expressions such as "(meth)acryloyl".

[0017] Examples of the (meth)acrylic acid ester compound (A) in the present invention are shown below.

[0018] Examples of the aromatic ring of the compound (A-1) having an aromatic ring include benzene, naphthalene, anthracene, biphenyl, benzophenone, phenyl ether, and bisphenol A. Bisphenol A is preferred because the mechanical strength and water resistance of the cured product are improved when combined with the mono(meth)acrylic acid ester compound (B). Examples of the compound (A-1) having an aromatic ring include 2,2-bis[4-[3-acryloyloxy-2-hydroxypropoxy]phenyl]propane, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (commonly known as "Bis-GMA"), 2,2-bis[4-[2-(acryloyloxy)ethoxy]phenyl]propane, 2,2-bis[4-[2-(methacryloyloxy)ethoxy]phenyl]propane (commonly known as "Bis-MEPP"), 2,2-bis[4-(meth)acryloyloxypolyethoxyphenyl]propane (e.g., those having an average added mole number of ethoxy groups of 2.6), 1,2-bis[3-(meth)acryloyloxy-2-hydroxypropoxyphenyl]ethane, and 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene. Among these, 2,2-bis[4-[3-acryloyloxy-2-hydroxypropoxy]phenyl]propane, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis[4-(meth)acryloyloxyethoxyphenyl]propane, and 2,2-bis[4-methacryloyloxypolyethoxyphenyl]propane (those with an average added mole number of ethoxy groups of 2.6 (commonly known as "D2.6E")) having a bisphenol A skeleton are more preferred from the viewpoint of mechanical strength after curing.

[0019] Examples of the alicyclic ring of the compound (A-2) having an alicyclic ring include cyclopentane, cyclohexane, cycloheptane, dicyclodecane, tricyclodecane, adamantane, isobornyl, etc. Examples of the compound (A-2) having an alicyclic ring include 1,4-cyclohexanedimethanol di(meth)acrylate, tricyclodecanedimethanol di(meth)acrylate, adamantyl di(meth)acrylate, adamantyl tri(meth)acrylate, etc.

[0020] Examples of the heterocyclic ring of the compound (A-3) having a heterocyclic ring include heterocyclic rings containing only nitrogen atoms as heteroatoms such as triazine, carbazole, pyrrolidin, and piperidine; heterocyclic rings containing only oxygen atoms as heteroatoms such as tetrahydrofuran, oxane, dioxane, and dioxolane; heterocyclic rings containing oxygen and nitrogen atoms as heteroatoms such as morpholine; heterocyclic rings containing only sulfur atoms as heteroatoms such as tetrahydrothiophene and tetrahydrothiopyran; heterocyclic rings containing sulfur and nitrogen atoms as heteroatoms such as thiazine and thiazole. Examples of the compound (A-3) having a heterocyclic ring include ethoxylated isocyanuric acid tri(meth)acrylate, ε-caprolactone-modified tris(2-(meth)acryloyloxyethyl)isocyanurate, and hydroxypivalaldehyde-modified trimethylolpropane di(meth)acrylate. A preferred embodiment of the present invention is a dental restorative hardenable composition that is substantially free of a compound (A-3) having a heterocycle and a polymerizable functional group. Another preferred embodiment of the present invention is a dental restorative hardenable composition that is substantially free of a compound having a heterocycle containing a nitrogen atom and a polymerizable functional group. The nitrogen atom-containing heterocycle includes a heterocycle containing only a nitrogen atom as the heteroatom, a heterocycle containing an oxygen atom and a nitrogen atom as the heteroatom, and a heterocycle containing a sulfur atom and a nitrogen atom as the heteroatom. "Substantially free of a compound having a heterocycle containing a nitrogen atom and a polymerizable functional group" means that the content of a compound having a heterocycle containing a nitrogen atom and a polymerizable functional group in the dental restorative hardenable composition is less than 0.1% by mass, preferably less than 0.05% by mass, more preferably less than 0.01% by mass, and even more preferably less than 0% by mass. "Substantially free of compound (A-3) having a heterocycle and a polymerizable functional group" also means not containing a compound (A-3) having a heterocycle and a polymerizable functional group in the same amount.

[0021] The (meth)acrylic acid ester compound (A) preferably contains a compound that does not have a hydrogen bond site, since it can suppress the decrease in mechanical strength due to water absorption through hydrogen bonds and has higher water resistance.Specifically, the (meth)acrylic acid ester compound (A) preferably contains a compound having a hydroxyl group, a carboxyl group, a primary amino group, a secondary amino group, an amide group, a urea bond, and a urethane bond, more preferably contains a compound that does not have a hydroxyl group, a carboxyl group, a primary amino group, a secondary amino group, an amide group, a urea bond, and a urethane bond and has a cyclic structure, more preferably contains a compound that does not have a hydroxyl group, a carboxyl group, a primary amino group, a secondary amino group, an amide group, a urea bond, and a urethane bond and has an aromatic ring, and particularly preferably contains a compound that does not have a hydroxyl group, a carboxyl group, a primary amino group, a secondary amino group, an amide group, a urea bond, and a urethane bond and has a bisphenol A skeleton. A preferred embodiment of the present invention is a hardenable composition for dental restoration, in which the compound (A-1) having an aromatic ring does not have a hydroxy group, a carboxy group, a primary amino group, a secondary amino group, an amide group, a urea bond, or a urethane bond, and includes a compound having an aromatic ring.

[0022] The weight average molecular weight (Mw) of the (meth)acrylic acid ester compound (A) is preferably from 500 to 50,000, more preferably from 750 to 30,000, and even more preferably from 1,000 to 15,000, from the viewpoints of paste workability and mechanical strength after curing.

[0023] The content of the (meth)acrylic acid ester compound (A) in the dental restoration hardenable composition of the present invention is preferably 10 to 99 mass% based on the total amount of the (meth)acrylic acid ester compound (A) and the mono(meth)acrylic acid ester compound (B), and from the viewpoints of superior mechanical strength, water resistance, and paste workability, it is more preferably 30 to 95 mass%, and even more preferably 50 to 90 mass%.

[0024] [Mono(meth)acrylic acid ester compound (B)] The mono(meth)acrylic acid ester compound (B) is used in the dental restorative hardenable composition of the present invention to reduce the viscosity of the dental restorative hardenable composition, impart excellent paste operability, and impart high mechanical strength and water resistance to the hardened product. The mono(meth)acrylic acid ester compound (B) may contain at least one selected from the group consisting of the mono(meth)acrylic acid ester compound (B-1) represented by the above general formula (I) (hereinafter, sometimes referred to as "mono(meth)acrylic acid ester compound (B-1)") and the mono(meth)acrylic acid ester compound (B-2) represented by the above general formula (II) (hereinafter, sometimes referred to as "mono(meth)acrylic acid ester compound (B-2)"). The mono(meth)acrylic acid ester compound (B-1) and the mono(meth)acrylic acid ester compound (B-2) will be described below. In the mono(meth)acrylic acid ester compound (B), the skeleton represented by the above general formula (I) and the skeleton represented by the above general formula (II) are rigid and hydrophobic, and therefore the obtained hardenable composition for dental restoration has low water absorption and can suppress a decrease in mechanical strength.

[0025] Each symbol in formula (I) will be explained. In formula (I), R 1 is a group represented by the above general formula (i) or a group represented by the above general formula (ii), and in the formula (i) or (ii), R 4 and R 6 R is independently a hydrogen atom or a methyl group. 3 and R 5are each independently a divalent hydrocarbon group having 1 to 10 carbon atoms. The hydrocarbon group preferably has 1 to 6 carbon atoms, more preferably has 1 to 4 carbon atoms, and even more preferably has 1 to 3 carbon atoms, in terms of good paste handling of the dental restorative hardenable composition obtained and excellent mechanical strength after hardening. Examples of the hydrocarbon group include a linear or branched alkylene group having 1 to 10 carbon atoms; a cycloalkylene group having 3 to 10 carbon atoms; and a phenylene group. k and l are each independently an integer of 0 to 6, and k is preferably 0 to 4, more preferably 0 to 3, even more preferably 0 to 2, and particularly preferably 0 or 1, in terms of low viscosity of the dental restorative hardenable composition obtained, suppression of bubble generation in the hardened product, and excellent hardening properties. Also, l is preferably 0 to 4, more preferably 0 to 2, and even more preferably 0 or 1.

[0026] Examples of the mono(meth)acrylic acid ester compound (B-1) include o-phenylphenol(meth)acrylate, m-phenylphenol(meth)acrylate, p-phenylphenol(meth)acrylate, methoxylated-o-phenylphenol(meth)acrylate, methoxylated-m-phenylphenol(meth)acrylate, methoxylated-p-phenylphenol(meth)acrylate, ethoxylated-o-phenylphenol(meth)acrylate, ethoxylated-m-phenylphenol(meth)acrylate, ethoxylated-p-phenylphenol(meth)acrylate, propoxylated-o-phenylphenol(meth)acrylate, propoxylated-m-phenylphenol(meth)acrylate, propoxylated-p-phenylphenol(meth)acrylate, butoxylated-o-phenylphenol(meth)acrylate, butoxylated-m-phenylphenol(meth)acrylate, and butoxylated-p-phenylphenol(meth)acrylate. These may be used alone or in combination of two or more. Among these, in terms of the paste of the dental restoration hardening composition obtained being easy to handle and having excellent mechanical strength after hardening, ethoxylated-o-phenylphenol acrylate, ethoxylated-m-phenylphenol acrylate, ethoxylated-p-phenylphenol acrylate, propoxylated-o-phenylphenol acrylate, propoxylated-m-phenylphenol acrylate, and propoxylated-p-phenylphenol acrylate are more preferred, ethoxylated-o-phenylphenol acrylate, ethoxylated-m-phenylphenol acrylate, and ethoxylated-p-phenylphenol acrylate are even more preferred, ethoxylated-o-phenylphenol acrylate and ethoxylated-m-phenylphenol acrylate are particularly preferred, and ethoxylated-o-phenylphenol acrylate is the most preferred.

[0027] Each symbol in formula (II) will be explained. In formula (II), X is a divalent hydrocarbon group having 1 to 6 carbon atoms or an oxygen atom, and an oxygen atom is preferred in terms of good workability of the paste of the resulting dental restorative hardenable composition and excellent mechanical strength after hardening.2 is a group represented by the above general formula (i) or general formula (ii), and in the formula (i) or (ii), R 4 and R 6 R is independently a hydrogen atom or a methyl group. 3 and R 5 are each independently a divalent hydrocarbon group having 1 to 10 carbon atoms. The hydrocarbon group preferably has 1 to 6 carbon atoms, more preferably has 1 to 4 carbon atoms, and even more preferably has 1 to 3 carbon atoms, from the viewpoint of good operability of the paste of the dental restorative hardenable composition obtained and excellent mechanical strength after hardening. Examples of the hydrocarbon group include a linear or branched alkylene group having 1 to 10 carbon atoms; a cycloalkylene group having 3 to 10 carbon atoms; and a phenylene group. k and l are each independently an integer of 0 to 6, and from the viewpoint of good operability of the paste of the dental restorative hardenable composition obtained and excellent mechanical strength after hardening, k is preferably 0 to 4, more preferably 0 to 3, even more preferably 0 to 2, and particularly preferably 0 or 1. Furthermore, l is preferably 0 to 4, more preferably 0 to 2, and even more preferably 0 or 1. In one preferred embodiment, the mono(meth)acrylic acid ester compound (B) includes a mono(meth)acrylic acid ester compound (B-2) represented by general formula (II). In another preferred embodiment, the mono(meth)acrylic acid ester compound (B) includes a mono(meth)acrylic acid ester compound (B-2) represented by general formula (II), X is an oxygen atom, and R 2 is a group represented by general formula (i). In another preferred embodiment, the mono(meth)acrylic acid ester compound (B) includes a mono(meth)acrylic acid ester compound (B-2) represented by general formula (II), X is an oxygen atom, and R 2 is a group represented by general formula (i), and k is 0 or 1.

[0028] Examples of the mono(meth)acrylic acid ester compound (B-2) include o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, p-phenoxybenzyl (meth)acrylate, 2-(o-phenoxyphenyl)ethyl (meth)acrylate, 2-(m-phenoxyphenyl)ethyl (meth)acrylate, 2-(p-phenoxyphenyl)ethyl (meth)acrylate, 3-(o-phenoxyphenyl)propyl (meth)acrylate, 3-(m-phenoxyphenyl)propyl (meth)acrylate, 3-(p-phenoxyphenyl)propyl (meth)acrylate, Examples of the acrylates include 4-(o-phenoxyphenyl)butyl (meth)acrylate, 4-(m-phenoxyphenyl)butyl (meth)acrylate, 4-(p-phenoxyphenyl)butyl (meth)acrylate, 5-(o-phenoxyphenyl)pentyl (meth)acrylate, 5-(m-phenoxyphenyl)pentyl (meth)acrylate, 5-(p-phenoxyphenyl)pentyl (meth)acrylate, 6-(o-phenoxyphenyl)hexyl (meth)acrylate, 6-(m-phenoxyphenyl)hexyl (meth)acrylate, and 6-(p-phenoxyphenyl)hexyl (meth)acrylate. These may be used alone or in combination of two or more. Among these, in terms of the ease of use of the resulting dental restoration hardenable composition paste and its excellent mechanical strength after hardening, o-phenoxybenzyl acrylate, m-phenoxybenzyl acrylate, p-phenoxybenzyl acrylate, 2-(o-phenoxyphenyl)ethyl acrylate, 2-(m-phenoxyphenyl)ethyl acrylate, and 2-(p-phenoxyphenyl)ethyl acrylate are more preferred, o-phenoxybenzyl acrylate, m-phenoxybenzyl acrylate, and p-phenoxybenzyl acrylate are even more preferred, o-phenoxybenzyl acrylate and m-phenoxybenzyl acrylate are particularly preferred, and m-phenoxybenzyl acrylate is the most preferred.

[0029] The content of the mono(meth)acrylic acid ester compound (B) in the dental restoration hardenable composition of the present invention is preferably 1.0 to 90 mass% based on the total amount of the (meth)acrylic acid ester compound (A) and the mono(meth)acrylic acid ester compound (B), and from the viewpoints of superior mechanical strength, water resistance, and paste workability, it is more preferably 5 to 80 mass%, and further preferably 10 to 70 mass%.

[0030] The polymerizable monomer contained in the dental restorative hardenable composition of the present invention may be substantially composed of only the (meth)acrylic acid ester compound (A) and the mono(meth)acrylic acid ester compound (B). The polymerizable monomer is substantially composed of only the (meth)acrylic acid ester compound (A) and the mono(meth)acrylic acid ester compound (B), which means that the content of the polymerizable monomer other than the (meth)acrylic acid ester compound (A) and the mono(meth)acrylic acid ester compound (B) is less than 10.0 mass%, preferably less than 5.0 mass%, more preferably less than 1.0 mass%, even more preferably less than 0.1 mass%, and particularly preferably less than 0.01 mass%, based on the total amount of the polymerizable monomer contained in the dental restorative hardenable composition.

[0031] [Inorganic filler (C)] As the inorganic filler (C) in the present invention, known inorganic particles used as a filler for dental composite resins can be used as long as the effect of the present invention is achieved. Examples of the inorganic particles include various glasses (e.g., silicon dioxide (quartz, quartz glass, silica gel, etc.), those containing silicon as the main component and various heavy metals together with boron and / or aluminum), alumina, various ceramics, diatomaceous earth, kaolin, clay minerals (montmorillonite, etc.), activated clay, synthetic zeolite, mica, silica, calcium fluoride, ytterbium fluoride, calcium phosphate, barium sulfate, zirconium dioxide (zirconia), titanium dioxide (titania), and hydroxyapatite. The inorganic filler may be used alone or in combination of two or more.

[0032] Important physical properties desired for dental materials include transparency and X-ray contrast similar to those of natural teeth. Of these, transparency can be achieved by matching the refractive index of the inorganic filler (C) with that of the polymer of the polymerizable monomer as closely as possible. On the other hand, X-ray contrast can be imparted by using an inorganic filler (oxide, etc.) containing a heavy metal element such as zirconium, barium, titanium, lanthanum, or strontium as the inorganic filler (C). The refractive index of such an inorganic filler containing a heavy metal element is usually high, within the range of 1.5 to 1.6. In the present invention, for example, the refractive index of a cured product of a (meth)acrylic acid ester compound (A) and a mono(meth)acrylic acid ester compound (B) having two or more (meth)acryloyloxy groups in one molecule constituting the polymerizable monomer that forms the polymer is usually within the range of 1.5 to 1.6, so that even when combined with such an inorganic filler having a high refractive index and X-ray contrast, the refractive index difference can be adjusted to be small, and the transparency of the resulting dental material can be improved.

[0033] Examples of inorganic fillers having a high refractive index that can impart the above-mentioned X-ray contrast properties include barium borosilicate glass (e.g., "E-3000" manufactured by Esstech, "8235", "GM27884", "GM39923" manufactured by Schott, etc.), strontium boroaluminosilicate glass (e.g., "E-4000" manufactured by Esstech, "G018-093", "GM32087" manufactured by Schott, etc.), lanthanum glass (e.g., "GM31684" manufactured by Schott, etc.), fluoroaluminosilicate glass (e.g., "GM31684" manufactured by Schott, etc.), and fluoroaluminosilicate glass (e.g., "GM31684" manufactured by Schott, etc.). Examples of such glasses include glasses containing zinc oxide (e.g., Schott's "G018-091" and "G018-117" and the like), glasses containing zirconia (e.g., Schott's "G018-310" and "G018-159" and the like), glasses containing strontium (e.g., Schott's "G018-163", "G018-093", "GM32087" and the like), glasses containing zinc oxide (e.g., Schott's "G018-161" and the like), and glasses containing calcium (e.g., Schott's "G018-309" and the like).

[0034] The shape of the inorganic filler (C) is not particularly limited, and various shapes can be used, such as crushed, plate-like, scaly, fibrous (short fiber, long fiber, etc.), needle-like, whisker-like, spherical, etc. The inorganic filler (C) may be a combination of different shapes among the above shapes as long as it satisfies the requirements of the present invention.

[0035] It is important that the average primary particle size of the inorganic filler (C) in the present invention is 0.01 to 5 μm. By using an inorganic filler (C) having an average primary particle size in this range, a dental restorative hardenable composition having excellent abrasive properties of the hardened product can be obtained. From this viewpoint, the average primary particle size of the inorganic filler (C) is preferably 0.02 μm or more, more preferably 0.04 μm or more, and preferably 3 μm or less, more preferably 2 μm or less. If the average primary particle size is smaller than 0.01 μm, the mechanical strength is likely to be impaired, and if it is larger than 5 μm, the abrasiveness may be impaired.

[0036] The average primary particle size of the inorganic filler (C) can be determined by a laser diffraction scattering method or by observing particles with an electron microscope. Specifically, the laser diffraction scattering method is convenient for measuring the particle size of particles of 0.1 μm or more, and the electron microscope observation is convenient for measuring the particle size of particles of less than 0.1 μm. The laser diffraction scattering method may be used to determine whether the average primary particle size is 0.1 μm or more.

[0037] In the laser diffraction scattering method, for example, the average primary particle diameter can be determined by measurement using a laser diffraction particle size distribution measuring device (e.g., "SALD-2300" manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.

[0038] In electron microscope observation, for example, an image of the particles is taken with a scanning electron microscope (SEM; for example, Hitachi High-Technologies Corporation's "SU3500H-800NA type," etc.), and the particle diameters of the particles (200 or more) observed within a unit field of view of the SEM image are measured using image analysis particle size distribution measurement software (Mountec Corporation's "Macview," etc.), to obtain the average primary particle diameter. In this case, the particle diameter of the particle is obtained as the equivalent circle diameter, which is the diameter of a circle having the same area as the area of ​​the particle, and the average primary particle diameter is calculated from the number of particles and their particle diameters.

[0039] The content of the inorganic filler (C) in the dental restorative hardenable composition of the present invention is not particularly limited, but is preferably 50 to 95 mass %, more preferably 55 to 90 mass %, and even more preferably 60 to 85 mass %, based on the total amount of the dental restorative hardenable composition.

[0040] The inorganic filler (C) in the present invention is preferably one that has been surface-treated in advance with a surface treatment agent. By using the surface-treated inorganic filler (C), the mechanical strength of the obtained dental restorative hardenable composition after hardening can be further improved. When two or more kinds of inorganic fillers (C) are used, only one of them may be surface-treated, or all of them may be surface-treated. In the latter case, the inorganic fillers (C) that have been individually surface-treated may be mixed, or a plurality of inorganic fillers may be mixed in advance and surface-treated collectively.

[0041] As the surface treatment agent, a known surface treatment agent can be used, and an organometallic compound such as an organosilicon compound, an organotitanium compound, an organozirconium compound, an organoaluminum compound, and an acidic group-containing organic compound having at least one acidic group such as a phosphoric acid group, a pyrophosphoric acid group, a thiophosphoric acid group, a phosphonic acid group, a sulfonic acid group, or a carboxylic acid group can be used. When two or more surface treatment agents are used, the surface treatment layer may be a mixture of two or more surface treatment agents, or a multi-layer structure in which a plurality of surface treatment layers are laminated. In addition, a known method can be used as the surface treatment method without any particular limitation.

[0042] The organosilicon compound is, for example, R 7 n SiY (4-n) (wherein R 7 represents a substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms, Y represents an alkoxy group having 1 to 4 carbon atoms, an acetoxy group, a hydroxyl group, a halogen atom, or a hydrogen atom, and n represents an integer of 0 to 3, provided that R 7 and when there are multiple Y's, they may be the same or different.

[0043] Specifically, for example, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, isobutyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, 3,3,3-trifluoropropyltrimethoxysilane, methyl-3,3,3-trifluoropropyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloyloxypropylmethyldimethoxysilane, γ-methacryloyloxypropylmethyldiethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, trimethylsilanol, methyltrichlorosilane, methyldichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, vinyltrichlorosilane, trimethylbromosilane, diethylsilane, vinyltriacetoxysilane, ω-(meth)acryloyloxyalkyltrimethoxysilane [number of carbon atoms between (meth)acryloyloxy group and silicon atom: 3 to 12, e.g., γ-methacryloyloxypropyltrimethoxysilane, etc.], ω-(meth)acryloyloxyalkyltriethoxysilane [number of carbon atoms between (meth)acryloyloxy group and silicon atom: 3 to 12, e.g., γ-methacryloyloxypropyltriethoxysilane, etc. In the present invention, the expression "(meth)acryloyloxy" is used to include both methacryloyloxy and acryloyloxy.

[0044] Among these, coupling agents having a functional group copolymerizable with a polymerizable monomer, such as ω-(meth)acryloyloxyalkyltrimethoxysilane [number of carbon atoms between the (meth)acryloyloxy group and the silicon atom: 3 to 12], ω-(meth)acryloyloxyalkyltriethoxysilane [number of carbon atoms between the (meth)acryloyloxy group and the silicon atom: 3 to 12], vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, and γ-glycidoxypropyltrimethoxysilane are preferably used.

[0045] Examples of the organic titanium compound include tetramethyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, and tetra(2-ethylhexyl) titanate.

[0046] Examples of the organic zirconium compound include zirconium isopropoxide, zirconium n-butoxide, zirconium acetylacetonate, and zirconium acetate.

[0047] Examples of the organoaluminum compound include aluminum acetylacetonate and aluminum organic acid salt chelate compounds.

[0048] Examples of the acidic group-containing organic compound containing a phosphoric acid group include 2-ethylhexyl acid phosphate, stearyl acid phosphate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxy Hexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate Hydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyicosyl dihydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, bis[4-(meth)acryloyloxybutyl]hydrogen phosphate, bis[6-(meth)acryloyloxyhexyl]hydrogen phosphate, bis[8-(meth)acryloyloxyhexyl]hydrogen phosphate, Examples of suitable hydrogen phosphates include bis[9-(meth)acryloyloxyoctyl]hydrogen phosphate, bis[9-(meth)acryloyloxynonyl]hydrogen phosphate, bis[10-(meth)acryloyloxydecyl]hydrogen phosphate, 1,3-di(meth)acryloyloxypropyl dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl-2-bromoethyl hydrogen phosphate, bis[2-(meth)acryloyloxy-(1-hydroxymethyl)ethyl]hydrogen phosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.

[0049] In addition, as the acidic group-containing organic compound having an acidic group such as a pyrophosphate group, a thiophosphate group, a phosphonic acid group, a sulfonic acid group, or a carboxylic acid group, for example, those described in WO 2012 / 042911 can be suitably used.

[0050] The surface treatment agent may be used alone or in combination of two or more. In order to increase the chemical bond between the inorganic filler (C) and the polymerizable monomer and improve the mechanical strength of the cured product, it is more preferable to use an acidic group-containing organic compound having a functional group copolymerizable with the polymerizable monomer.

[0051] The amount of the surface treatment agent used is not particularly limited, and is preferably, for example, 0.1 to 50 parts by mass per 100 parts by mass of the inorganic filler (C).

[0052] [Polymerization initiator (D)] Next, the polymerization initiator (D) will be described. Examples of the polymerization initiator (D) include a thermal polymerization initiator, a photopolymerization initiator, and a chemical polymerization initiator. These may be used alone or in combination of two or more.

[0053] Examples of the thermal polymerization initiator include organic peroxides and azo compounds.

[0054] Examples of the organic peroxide include ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates.

[0055] Examples of the ketone peroxide include methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, methylcyclohexanone peroxide, and cyclohexanone peroxide.

[0056] Examples of the hydroperoxide include 2,5-dimethylhexane-2,5-dihydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.

[0057] Examples of the diacyl peroxide include acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, decanoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide.

[0058] Examples of the dialkyl peroxide include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne.

[0059] Examples of the peroxyketals include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, and 4,4-bis(t-butylperoxy)valeric acid-n-butyl ester.

[0060] Examples of the peroxy ester include α-cumyl peroxy neodecanoate, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, 2,2,4-trimethylpentyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, di-t-butyl peroxy isophthalate, di-t-butyl peroxy hexahydroterephthalate, t-butyl peroxy-3,3,5-trimethylhexanoate, t-butyl peroxy acetate, t-butyl peroxy benzoate, and t-butyl peroxy maleic acid.

[0061] Examples of the peroxydicarbonate include di-3-methoxyperoxydicarbonate, di(2-ethylhexyl)peroxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, diisopropylperoxydicarbonate, di-n-propylperoxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, and diallylperoxydicarbonate.

[0062] Among these organic peroxides, diacyl peroxides are preferably used from the viewpoint of the overall balance of safety, storage stability, and radical generating ability, and among them, benzoyl peroxide is more preferably used.

[0063] Examples of the azo compound include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), dimethyl-2,2'-azobis(isobutyrate), and 2,2'-azobis(2-amidinopropane) dihydrochloride.

[0064] Examples of the photopolymerization initiator include (bis)acylphosphine oxides, α-diketones, and coumarins.

[0065] Among the (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, benzoyldi(2,6-dimethylphenyl)phosphonate, and salts thereof. Examples of the bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide, and salts thereof.

[0066] Among these (bis)acylphosphine oxides, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoylphenylphosphine oxide sodium salt are preferred.

[0067] Examples of the α-diketones include diacetyl, benzyl, camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4′-oxybenzyl, acenaphthenequinone, etc. Among these, camphorquinone is preferred.

[0068] Examples of the coumarins include 3,3'-carbonylbis(7-diethylaminocoumarin), 3-(4-methoxybenzoyl)coumarin, 3-thienoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, and 3-(p-nitrobenzoyl)coumarin. 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromocoumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 7-methoxy-3-(p-nitro benzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzoyl)benzo[f]coumarin , 3-(4-ethoxycinnamoyl)-7-methoxycoumarin, 3-(4-dimethylaminocinnamoyl)coumarin, 3-(4-diphenylaminocinnamoyl)coumarin, 3-[(3-dimethylbenzothiazol-2-ylidene)acetyl]coumarin, 3-[(1-methylnaphtho[1,2-d]thiazol-2-ylidene)acetyl]coumarin, 3,3'-carbonylbis(6-methoxycoumarin), 3,3'-carbonylbis(7-acetoxycoumarin), 3,3'-Carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylaminocoumarin), 3,3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin Examples of compounds include those described in JP-A-9-3109 and JP-A-10-245525, such as phosphorus, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, and 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one.

[0069] Among the above-mentioned coumarins, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are preferred.

[0070] Among these photopolymerization initiators, it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides, α-diketones, and coumarins, which are widely used in dental applications.

[0071] Furthermore, the photopolymerization initiator may be further combined with a polymerization promoter as necessary, whereby photopolymerization can be efficiently carried out in a shorter time.

[0072] Examples of polymerization accelerators suitable for photopolymerization initiators include tertiary amines, aldehydes, compounds having a thiol group, sulfinic acid and its salts, borate compounds, triazine compounds, etc. The polymerization accelerators may be used alone or in combination of two or more. In a preferred embodiment, the hardenable composition for dental restoration includes a polymerization initiator (D) containing a photopolymerization initiator, a polymerization accelerator for the photopolymerization initiator, and the polymerization accelerator is a tertiary amine.

[0073] Examples of tertiary amines include N,N-dimethylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, and N,N-dimethyl-3,5-di-t-butylaniline. N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-di(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-diisopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, Propylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, 4-(N,N-dimethylamino)benzoate n-butoxyethyl, 4-(N,N-dimethylamino)benzoate (2-methacryloyloxy)ethyl, 4-(N,N-dimethylamino)benzoate ethyl, 4-(N,N-dimethylamino)benzoate butyl, N-methyldiethanolamine, 4-(N,N-dimethylamino)benzophenone, trimethylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, triethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, and the like.

[0074] Examples of the aldehydes include dimethylaminobenzaldehyde, terephthalaldehyde, etc. Examples of the compounds having a thiol group include 2-mercaptobenzoxazole, decanethiol, 3-mercaptopropyltrimethoxysilane, thiobenzoic acid, etc.

[0075] Examples of sulfinic acid and its salts include benzenesulfinic acid, sodium benzenesulfinate, potassium benzenesulfinate, calcium benzenesulfinate, lithium benzenesulfinate, p-toluenesulfinic acid, sodium p-toluenesulfinate, potassium p-toluenesulfinate, calcium p-toluenesulfinate, lithium p-toluenesulfinate, 2,4,6-trimethylbenzenesulfinic acid, sodium 2,4,6-trimethylbenzenesulfinate, potassium 2,4,6-trimethylbenzenesulfinate, and 2,4,6-trimethylbenzenesulfinate. Examples of such sulfinates include calcium benzenesulfinate, lithium 2,4,6-trimethylbenzenesulfinate, 2,4,6-triethylbenzenesulfinic acid, sodium 2,4,6-triethylbenzenesulfinate, potassium 2,4,6-triethylbenzenesulfinate, calcium 2,4,6-triethylbenzenesulfinate, 2,4,6-triisopropylbenzenesulfinic acid, sodium 2,4,6-triisopropylbenzenesulfinate, potassium 2,4,6-triisopropylbenzenesulfinate, and calcium 2,4,6-triisopropylbenzenesulfinate.

[0076] As the chemical polymerization initiator, organic peroxides and amines; redox polymerization initiators such as organic peroxides, amines, and sulfinic acid (or its salt) are preferably used. When using a redox polymerization initiator, the oxidizing agent and the reducing agent are packaged separately, and the two must be mixed immediately before use. An example of the oxidizing agent for the redox polymerization initiator is an organic peroxide. The organic peroxide used as the oxidizing agent for the redox polymerization initiator is not particularly limited, and known organic peroxides can be used. Specifically, the organic peroxides exemplified in the heat polymerization initiator are mentioned above.

[0077] Among these organic peroxides, diacyl peroxides are preferably used from the viewpoint of the overall balance of safety, storage stability, and radical generating ability, and among them, benzoyl peroxide is more preferably used.

[0078] As a reducing agent for a redox polymerization initiator, a tertiary aromatic amine having no electron-withdrawing group in the aromatic ring is usually used. Examples of tertiary aromatic amines having no electron-withdrawing group in the aromatic ring include N,N-dimethylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, N,N-dimethyl-3,5-di-t-butylaniline, N,N-bis(2-hydroxyethyl) ... N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-diisopropylaniline, and N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline.

[0079] The chemical polymerization initiator may be used in combination with a polymerization accelerator as necessary. The polymerization accelerator for the chemical polymerization initiator may be selected from polymerization accelerators used in general industry, and among them, polymerization accelerators used for dental applications are preferably used. The polymerization accelerator may be used alone or in combination of two or more. Specific examples of the polymerization accelerator for the chemical polymerization initiator include amines, sulfinic acid and its salts, copper compounds, tin compounds, barbituric acid derivatives, vanadium compounds, and the like. In a preferred embodiment, the polymerization initiator (D) includes a chemical polymerization initiator, and further includes a polymerization accelerator for the chemical polymerization initiator, and the polymerization accelerator is an amine.

[0080] Amines used as polymerization accelerators for chemical polymerization initiators are divided into aliphatic amines and aromatic amines having an electron-withdrawing group on the aromatic ring. Examples of aliphatic amines include primary aliphatic amines such as n-butylamine, n-hexylamine, and n-octylamine; secondary aliphatic amines such as diisopropylamine, dibutylamine, and N-methylethanolamine; and tertiary aliphatic amines such as N-methyldiethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among these, tertiary aliphatic amines are preferred from the viewpoint of curability and storage stability of the composition, and N-methyldiethanolamine and triethanolamine are more preferably used.

[0081] In addition, examples of tertiary aromatic amines having an electron-withdrawing group in an aromatic ring used as a polymerization accelerator for a chemical polymerization initiator include ethyl 4-(N,N-dimethylamino)benzoate, methyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate, 2-(methacryloyloxy)ethyl 4-N,N-dimethylaminobenzoate, 4-(N,N-dimethylamino)benzophenone, butyl 4-(N,N-dimethylamino)benzoate, etc. Among these, from the viewpoint of imparting excellent curability to the composition, at least one selected from the group consisting of N,N-di(2-hydroxyethyl)-p-toluidine, ethyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate, and 4-(N,N-dimethylamino)benzophenone is preferably used.

[0082] Examples of the sulfinic acid and its salts used as the polymerization accelerator include those exemplified as the polymerization accelerator for the photopolymerization initiator described above, and sodium benzenesulfinate, sodium p-toluenesulfinate, and sodium 2,4,6-triisopropylbenzenesulfinate are preferred.

[0083] As the copper compound used as the polymerization accelerator, for example, copper acetylacetonate, copper acetate, copper oleate, copper chloride, copper bromide, etc. are preferably used.

[0084] Examples of tin compounds used as polymerization accelerators include di-n-butyltin dimaleate, di-n-octyltin dimaleate, di-n-octyltin dilaurate, di-n-butyltin dilaurate, etc. Particularly suitable tin compounds are di-n-octyltin dilaurate and di-n-butyltin dilaurate.

[0085] Among these, for dental composite resins, it is preferable to use a photopolymerization initiator because of the ease of hardening in the oral cavity, while for dental mill blanks, it is preferable to use a thermal polymerization initiator because it increases the degree of polymerization and improves strength.

[0086] The content of the polymerization initiator (D) in the present invention is not particularly limited, but from the viewpoint of the curability of the obtained composition, it is preferably 0.001 to 30 parts by mass relative to 100 parts by mass of the polymerizable monomer. When the content of the polymerization initiator (D) is 0.001 parts by mass or more relative to 100 parts by mass of the polymerizable monomer, the polymerization proceeds sufficiently and there is no risk of a decrease in mechanical strength, and it is more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more. On the other hand, when the content of the polymerization initiator (D) is 30 parts by mass or less relative to 100 parts by mass of the polymerizable monomer, sufficient mechanical strength is obtained even when the polymerization performance of the polymerization initiator itself is low, and there is no risk of precipitation from the composition, and it is more preferably 20 parts by mass or less.

[0087] The dental restorative hardenable composition of the present invention may contain a polymer, particularly a prepolymer, from the viewpoint of reducing polymerization shrinkage stress. In addition, dental composite resins are generally polymerized and cured by light irradiation, and during curing, polymerization shrinkage stress is applied to the adhesive interface between the cavity wall and the composite resin. If this polymerization shrinkage stress is large, a contraction gap may occur at the adhesive interface, which may cause secondary caries, dental pulp stimulation, coloring, and the fall-off of the cured product. Therefore, if the composition also has the effect of further reducing polymerization shrinkage stress, it can be said to be a more preferable dental composite resin. In particular, when the dental restorative hardenable composition of the present invention is used as a dental composite resin, the cured product has high mechanical strength and excellent properties such as water resistance and abrasiveness, and in addition, the effect of reducing polymerization shrinkage stress is more excellent, so that the dental restorative hardenable composition of the present invention preferably contains a polymer, particularly a prepolymer. A prepolymer is an intermediate product in which the polymerization of a polymerizable monomer is stopped at an appropriate point, or a polymer in which a polymerizable functional group is introduced after polymerization, and both have unreacted polymerizable functional groups, allowing further polymerization. The prepolymers may be used alone or in combination of two or more kinds.

[0088] [Prepolymer] The type of unreacted polymerizable functional group that the prepolymer has is not particularly limited. Examples of the polymerizable functional group include a carbon-carbon double bond, a vinyl group, a vinyloxy group, a (meth)allyl group, a (meth)acryloyl group, a maleoyl group, a styryl group, and a cinnamoyl group. As the polymerizable functional group, a (meth)acryloyl group is preferable, and a (meth)acryloyloxy group and a (meth)acrylamide group are more preferable. The number of unreacted polymerizable functional groups in the prepolymer is preferably 1 or more, more preferably 2 or more, on average per molecule of the prepolymer, more preferably 5 or more, particularly preferably 10 or more, and may be 15 or more, 20 or more, or even 25 or more, and is preferably 1,000 or less, more preferably 500 or less, more preferably 100 or less, particularly preferably 50 or less, because the effect of reducing the polymerization shrinkage stress is more excellent. There is no particular restriction on the method for measuring the number of unreacted polymerizable functional groups in the prepolymer, but for example, the concentration (mol / g) of the unreacted polymerizable functional groups in the prepolymer is obtained by NMR measurement, and the concentration can be obtained by multiplying the concentration by the weight average molecular weight of the prepolymer described later, and more specifically, the method described in the examples can be used.

[0089] The molecular weight of the prepolymer is not particularly limited, but the weight average molecular weight of the prepolymer is preferably 1,000 or more because the effect of the present invention is more pronounced, more preferably 5,000 or more because the effect of reducing the polymerization shrinkage stress is more excellent, and even more preferably 10,000 or more, and is preferably 1,000,000 or less, and more preferably 500,000 or less because the effect of reducing the polymerization shrinkage stress is more excellent, more preferably 300,000 or less, particularly preferably 100,000 or less, and may be 80,000 or less, or even 60,000 or less. The method for measuring the weight average molecular weight of the prepolymer is not particularly limited, but it can be measured by GPC measurement, etc., and more specifically, it can be measured by the method described later in the examples.

[0090] The prepolymer content in the dental restorative hardenable composition of the present invention is not particularly limited, but from the viewpoints of the consistency stability, polymerization shrinkage stress, and operability of the obtained dental restorative hardenable composition, and further the mechanical strength of the obtained cured product, the prepolymer content is preferably 0.5 mass % or more, more preferably 1 mass % or more, and even more preferably 3 mass % or more, based on the mass of the dental restorative hardenable composition, and is preferably 20 mass % or less, more preferably 18 mass % or less, even more preferably 16 mass % or less, and may be 12 mass % or less, or even 8 mass % or less.

[0091] In addition to the above-mentioned components, the dental restorative hardenable composition of the present invention may further contain, depending on the purpose, a pH adjuster, an ultraviolet absorber, an antioxidant, a colorant (e.g., a pigment), a chain transfer agent, an antibacterial agent, an X-ray contrast agent, a thickener, a fluorescent agent, etc. These may be used alone or in combination of two or more.

[0092] The pigment may be any known pigment used in dental composite resin without any restrictions.The pigment may be any inorganic pigment and / or organic pigment, and examples of the inorganic pigment include chromates such as yellow lead, zinc yellow, and barium yellow; ferrocyanides such as iron blue; sulfides such as vermilion, cadmium yellow, zinc sulfide, and cadmium red; sulfates such as barium sulfate, zinc sulfate, and strontium sulfate; oxides such as antimony white, zinc white, titanium white, red iron oxide, iron black, and chromium oxide; hydroxides such as aluminum hydroxide; silicates such as calcium silicate and ultramarine; carbon such as carbon black and graphite. Examples of organic pigments include nitroso compounds such as naphthol green B and naphthol green Y; nitro pigments such as naphthol yellow S and lithol fast yellow 2G; insoluble azo pigments such as permanent red 4R, brilliant fast scarlet, hansa yellow, and benzidine yellow; poorly soluble azo pigments such as lithol red, lake red C, and lake red D; soluble azo pigments such as brilliant carmine 6B, permanent red F5R, pigment scarlet 3B, and bordeaux 10B; phthalocyanine pigments such as phthalocyanine blue, phthalocyanine green, and sky blue; basic compounds such as rhodamine lake, malachite green lake, and methyl violet lake; and acidic compounds such as peacock blue lake, eosine lake, and quinoline yellow lake. The pigments may be used alone or in combination of two or more, and are appropriately selected according to the desired color tone.

[0093] The content of the pigment in the dental restorative hardenable composition is not particularly limited since it is appropriately adjusted according to the desired color tone, but is preferably 0.000001 parts by mass or more, more preferably 0.00001 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 1 part by mass or less, in 100 parts by mass of the dental restorative hardenable composition. The content of the pigment is preferably 0.000001 to 5 parts by mass, more preferably 0.00001 to 1 part by mass, in 100 parts by mass of the dental restorative hardenable composition.

[0094] Examples of the chain transfer agent include mercaptan compounds (n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, hexadecyl mercaptan, n-octadecyl mercaptan, etc.), halogen compounds (carbon tetrachloride, methylene chloride, bromoform, etc.), unsaturated hydrocarbon compounds (2,4-diphenyl-4-methyl-1-pentene, α-terpinene, dipentene, terpinolene, etc.), thiols (mercaptoacetic acid, 2-ethylhexyl mercaptoacetate, 3-methoxybutyl mercaptoacetate, β-mercaptopropionic acid, methyl β-mercaptopropionate, 2-ethylhexyl β-mercaptopropionate, 3-methoxybutyl β-mercaptopropionate, 2-mercaptoethanol, 3-mercapto-1,2-propanediol, etc.).

[0095] The method for producing the dental restorative hardenable composition of the present invention includes, for example, the following steps (1) and (2). (1) Mixing process The kneading step is a step of kneading work, in which a (meth)acrylic acid ester compound (A), a mono(meth)acrylic acid ester compound (B) and a polymerization initiator (D) are charged into a kneader container to prepare a polymerizable monomer-containing composition, and then an inorganic filler (C) is further charged and kneaded to prepare a paste-like composition. In the kneading step, the kneading method is not particularly limited as long as the effects of the present invention are achieved, and a known method can be adopted, but from the viewpoint of shortening the kneading time and preventing the occurrence of variations in the properties of the paste, it is preferable to knead while heating. The kneading temperature is preferably 40 to 60°C. If the temperature is lower than 40°C, the effect of shortening the kneading time cannot be sufficiently obtained, and if the temperature exceeds 60°C, polymerization hardening or deterioration of the composition may occur during kneading. In addition, during kneading, a vacuum degassing process can be performed as necessary. At this time, the degree of vacuum is not particularly limited, but in order to efficiently remove air bubbles, the degree of vacuum is preferably 5 to 200 Torr. (2) Defoaming process The defoaming step is a step of performing a defoaming operation, in which the paste-like composition is put into a defoaming machine container, and then the paste is defoamed by pushing it out of the container while applying pressure while removing bubbles from the inside of the paste by reducing pressure. The defoaming conditions are not particularly limited, but in order to efficiently remove bubbles, and to suppress separation of the polymerizable monomer-containing composition containing the (meth)acrylic acid ester compound (A), the mono(meth)acrylic acid ester compound (B) and the polymerization initiator (D) from the inorganic filler (C), the vacuum degree is preferably 5 to 200 Torr. The decompression time is preferably 3 to 30 minutes. The pressure during extrusion is preferably 0.5 to 5 MPa. The pressurization time is preferably 3 to 30 minutes. During defoaming, a heat treatment can also be performed as necessary. At this time, the temperature is not particularly limited, but in order to efficiently remove bubbles, the temperature is preferably 40 to 60°C.

[0096] The dental restorative hardenable composition of the present invention has excellent paste operability, and the cured product has high mechanical strength, water resistance, and abrasiveness, and therefore can be suitably used as a dental material. Specifically, in the field of dental medicine, it can be suitably used as a dental material (particularly a dental composite resin) that can replace a part or the whole of a natural tooth. In addition, the cured product obtained by polymerizing and curing the dental restorative hardenable composition of the present invention can be suitably used as a dental mill blank, which is a cut material used in a CAD / CAM system that is cut by a milling device. When used as a dental composite resin, the flexural modulus of the cured product of the dental restorative hardenable composition is preferably 8 GPa or more. When used as a dental mill blank, the flexural modulus of the cured product of the dental restorative hardenable composition is preferably 12 GPa or more. The flexural modulus of the cured product of the dental restorative hardenable composition is not particularly limited, but may be 30 GPa or less because if it is too high, the tooth substance may be damaged by wear, fracture, etc. EXAMPLES

[0097] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0098] [(Meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups in one molecule] D2.6E: 2,2-bis[4-methacryloyloxypolyethoxyphenyl]propane (average number of moles of ethoxy groups added: 2.6) (manufactured by Shin-Nakamura Chemical Co., Ltd.) Bis-MEPP: 2,2-bis[4-[2-(methacryloyloxy)ethoxy]phenyl]propane (manufactured by Shin-Nakamura Chemical Co., Ltd.) Bis-GMA: 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (manufactured by Shin-Nakamura Chemical Co., Ltd.) DCP: Tricyclodecane dimethanol dimethacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) UDMA: [2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)]dimethacrylate (Kyoeisha Chemical Co., Ltd.) TEGDMA: Triethylene glycol dimethacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0099] [Mono(meth)acrylic acid ester compound (B)] POBA: m-phenoxybenzyl acrylate (Kyoeisha Chemical Co., Ltd.) POBMA: m-phenoxybenzyl methacrylate (Kyoeisha Chemical Co., Ltd.) EPPA: Ethoxylated o-phenylphenol acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) [Mono(meth)acrylic acid ester compounds] MMA: Methyl methacrylate (Kuraray Co., Ltd.) IBMA: Isobornyl methacrylate (Kyoeisha Chemical Co., Ltd.) DDMA: Dodecyl methacrylate (Kyoeisha Chemical Co., Ltd.)

[0100] [Mono (meth)acrylamide compounds] HEAA: N-hydroxyethylacrylamide

[0101] [Inorganic filler (C)] UF2.0: Barium glass (average primary particle size 2.0 μm, manufactured by Schott) UF1.5: Barium glass (average primary particle size 1.5 μm, manufactured by Schott) UF0.7: Barium glass (average primary particle size 0.7 μm, manufactured by Schott) NF180: Barium glass (average primary particle size 0.180 μm, manufactured by Schott) Ar130: Fine particle silica (average primary particle diameter 0.016 μm, manufactured by Nippon Aerosil Co., Ltd.) Ox50: Fine particle silica (average primary particle diameter 0.04 μm, manufactured by Nippon Aerosil Co., Ltd.) [Surface treatment agent] γ-MPS: γ-methacryloyloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.) 11-MUS: 11-methacryloyloxydodecyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.) [Surface-treated inorganic filler] Inorganic filler (C6): amorphous silica-zirconia, surface treated with γ-methacryloyloxypropyltrimethoxysilane, average particle size: 4.2 μm, refractive index: 1.54 Inorganic filler (C7): spherical silica-zirconia, surface treated with γ-methacryloyloxypropyltrimethoxysilane, average particle size: 0.1 μm, refractive index: 1.52

[0102] [Polymerization initiator (D)] CQ: Camphorquinone (photopolymerization initiator) (Tokyo Chemical Industry Co., Ltd.) TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (BASF Japan Ltd.) THP: 1,1,3,3-tetramethylbutyl hydroperoxide (thermal polymerization initiator) (manufactured by NOF Corporation) BPO: Benzoyl peroxide (thermal polymerization initiator) (manufactured by NOF Corporation)

[0103] [Polymerization accelerator] JJA: Ethyl 4-(N,N-dimethylamino)benzoate DEPT: N,N-bis(2-hydroxyethyl)-p-toluidine

[0104] [Chain transfer agent] DPMP: 2,4-diphenyl-4-methyl-1-pentene (Tokyo Chemical Industry Co., Ltd.)

[0105] [Production Example 1 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M1) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of D2.6E and 30 parts by mass of POBA.

[0106] [Production Example 2 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M2) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 90 parts by mass of D2.6E and 10 parts by mass of POBA.

[0107] [Production Example 3 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M3) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 50 parts by mass of D2.6E and 50 parts by mass of POBA. [Production Example 4 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M4) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of D2.6E and 30 parts by mass of POBMA.

[0108] [Production Example 5 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M5) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of D2.6E and 30 parts by mass of EPPA.

[0109] [Production Example 6 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M6) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of Bis-MEPP and 30 parts by mass of POBA.

[0110] [Production Example 7 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M7) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of Bis-GMA and 30 parts by mass of POBA.

[0111] [Production Example 8 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M8) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of DCP and 30 parts by mass of POBA.

[0112] [Production Example 9 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M9) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of D2.6E and 30 parts by mass of TEGDMA.

[0113] [Production Example 10 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M10) was prepared by dissolving 2 parts by mass of BPO as a thermal polymerization initiator and 2 parts by mass of DEPT as a polymerization accelerator in 40 parts by mass of D2.6E, 30 parts by mass of Bis-GMA, and 30 parts by mass of TEGDMA.

[0114] [Production Example 11 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M11) was prepared by dissolving 1 part by mass of CQ as a photopolymerization initiator, 1.25 parts by mass of TPO, and 1.5 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of D2.6E, 30 parts by mass of TEGDMA, and 4 parts by mass of HEAA.

[0115] [Production Example 12 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M12) was prepared by dissolving 0.2 parts by mass of CQ as a photopolymerization initiator, 0.25 parts by mass of TPO, and 0.3 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of D2.6E and 30 parts by mass of MMA.

[0116] [Production Example 13 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M13) was prepared by dissolving 0.5 parts by mass of THP as a thermal polymerization initiator and 1.5 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of D2.6E and 30 parts by mass of POBA.

[0117] [Production Example 14 of Polymerizable Monomer-Containing Composition] A polymerizable monomer-containing composition (M14) was prepared by dissolving 1.5 parts by mass of BPO as a thermal polymerization initiator and 1.5 parts by mass of JJA as a polymerization accelerator in 70 parts by mass of UDMA and 30 parts by mass of TEGDMA.

[0118] The composition of each polymerizable monomer-containing composition is shown in Table 1 below.

[0119] [Table 1]

[0120] [Inorganic filler production example 1] 100 parts by mass of NF180 was dispersed in 300 parts by mass of ethanol, and 7 parts by mass of γ-MPS, 0.15 parts by mass of acetic acid, and 5 parts by mass of water were added and stirred at room temperature for 2 hours. The solvent was distilled off under reduced pressure, and the mixture was further surface-treated by drying at 90°C for 3 hours to obtain an inorganic filler (C1).

[0121] [Inorganic filler production example 2] A mixture of 80 parts by mass of UF2.0 and 20 parts by mass of NF180 was dispersed in 300 parts by mass of ethanol, and 2.25 parts by mass of γ-MPS, 0.15 parts by mass of acetic acid, and 5 parts by mass of water were added and stirred at room temperature for 2 hours. The solvent was distilled off under reduced pressure, and the mixture was further surface-treated by drying at 90°C for 3 hours to obtain an inorganic filler (C2).

[0122] [Inorganic filler production example 3] 100 parts by mass of NF180 was dispersed in 300 parts by mass of ethanol, 11 parts by mass of 11-MUS, 0.15 parts by mass of acetic acid, and 5 parts by mass of water were added, and the mixture was stirred at room temperature for 2 hours. The solvent was distilled off under reduced pressure, and the mixture was further surface-treated by drying at 90°C for 3 hours to obtain an inorganic filler (C3).

[0123] [Inorganic filler production example 4] A mixture of 90 parts by mass of UF0.7 and 10 parts by mass of Ar130 was dispersed in 300 parts by mass of ethanol, and 4 parts by mass of 11-MUS, 0.15 parts by mass of acetic acid, and 5 parts by mass of water were added and stirred at room temperature for 2 hours. The solvent was distilled off under reduced pressure, and the mixture was further surface-treated by drying at 90°C for 3 hours to obtain an inorganic filler (C4).

[0124] [Inorganic filler production example 5] A mixture of 100 parts by mass of UF1.5 and 20 parts by mass of Ox50 was dispersed in 300 parts by mass of toluene, 4 parts by mass of γ-MPS was added, and the mixture was heated under reflux for 2 hours. The solvent was distilled off under reduced pressure, and the mixture was further dried at 90°C for 3 hours to obtain an inorganic filler (C5) having an inorganic filler surface-treated with a surface treatment agent.

[0125] The compositions of the inorganic fillers (C1) to (C5) are shown in Table 2 below.

[0126] [Table 2]

[0127] [Prepolymer Production Examples 1 to 3] The mono(meth)acrylic acid ester compound, mono(meth)acrylic acid ester compound (B) and (meth)acrylic acid ester compound (A) in the amounts shown in Table 3 were used as polymerizable monomers, and these and toluene (5 times the total mass of the mono(meth)acrylic acid ester compound and the (meth)acrylic acid ester compound) were placed in a three-neck flask and dissolved, followed by nitrogen bubbling for 30 minutes. The chain transfer agent and polymerization initiator in the amounts shown in Table 3 were added thereto and stirred to obtain a toluene solution. This toluene solution was heated and stirred under reflux at 80°C in an oil bath. After 240 minutes, the heating was stopped and the solution was dropped into hexane (6 times the mass of the toluene solution) to obtain a precipitate that settled to the bottom. This was dried overnight at room temperature under reduced pressure to obtain prepolymers (P1) to (P3) in the form of white powder.

[0128] The compositions of the prepolymers (P1) to (P3) are shown in Table 3 below.

[0129] [Table 3]

[0130] [Weight average molecular weight of prepolymer] The weight-average molecular weight of the prepolymer was determined by GPC measurement. That is, tetrahydrofuran was used as the eluent, and two "TSKgel SuperMultipore HZM-M" columns manufactured by Tosoh Corporation and a "TSKgel SuperHZ4000" were connected in series as the column. In addition, a "HLC-8320GPC" manufactured by Tosoh Corporation equipped with a differential refractive index detector (RI detector) was used as the GPC device. For the measurement, first, 4 mg of the prepolymer was dissolved in 5 mL of tetrahydrofuran to prepare a sample solution. Next, the temperature of the column oven was set to 40°C, and 20 μL of the sample solution was injected at an eluent flow rate of 0.35 mL / min to measure the chromatogram of the prepolymer. Meanwhile, 10 standard polystyrene points with molecular weights in the range of 400 to 5,000,000 were measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight was created. Based on this calibration curve, the weight-average molecular weight of the prepolymer was determined from the chromatogram of the prepolymer measured as described above (n=1).

[0131] [Number of unreacted polymerizable functional groups in the prepolymer (average per molecule)] 1 The concentration ρ (mol / g) of unreacted polymerizable functional groups in the prepolymer was determined by H-NMR measurement, and the weight average molecular weight (M w ) multiplied by (ρ×M w ) was calculated, and this was taken as the number of unreacted polymerizable functional groups in the prepolymer (average per molecule). In addition, 1 In the H-NMR measurement, approximately 30 mg of the prepolymer and approximately 2 mg of dimethyl terephthalate (molecular weight: 194.19) as an internal standard were weighed (the weight of the prepolymer was P (mg), and the weight of dimethyl terephthalate is W DThe mixture was dissolved in 3 mL of deuterated chloroform. Then, using a nuclear magnetic resonance spectrometer (Bruker's "ULTRA SHIELD 400 PLUS"), measurements were performed at room temperature with 16 accumulations. From the integral values ​​of the proton peaks derived from the methacryloyl groups (5.55 ppm and 6.12 ppm) and the integral value of the aromatic proton peak of dimethyl terephthalate (8.10 ppm), the molar ratio of methacryloyl groups to dimethyl terephthalate (R P / D ) was sought. R P / D =[(I 5.55 +I 6.12 ) / 2] / (I 8.10 / 4) (Here, I 5.55 indicates the integral value of the peak at 5.55 ppm, and I 6.12 indicates the integral value of the peak at 6.12 ppm, and I 8.10 indicates the integral value of the peak at 8.10 ppm.) The molar ratio of the obtained methacryloyl group to dimethyl terephthalate (R P / D ) was used to calculate the concentration ρ [mol / g] of the polymerizable functional group in the prepolymer using the following formula (n=1). ρ = [R P / D ×W D / 194.19] / W P (Where, D indicates the weight of dimethyl terephthalate (mg), and W P indicates the weight of the prepolymer (mg).

[0132] Test Example 1 [Mechanical strength (three-point bending test)] Regarding the dental composite resin, the dental restorative hardenable composition of each Example and Comparative Example was vacuum degassed, filled into a stainless steel mold (dimensions: 2 mm x 2 mm x 25 mm), pressed against the top and bottom with slide glass, and hardened by irradiating light on both sides with a dental polymerization LED light irradiator (product name "PenCure 2000", manufactured by Morita Corporation) for 10 seconds at each point, 5 points on each side. Five hardened samples were prepared for each Example and Comparative Example. After removing the hardened sample from the mold, the flexural strength and flexural modulus of the hardened sample were measured using a universal testing machine (manufactured by Shimadzu Corporation, product name "AG-I 100kN") under conditions of a support distance of 20 mm and a crosshead speed of 1 mm / min, and the average values ​​of the measured values ​​of each sample were calculated to be the flexural strength and flexural modulus. The dental mill blanks were measured in the same manner as the dental composite resin samples, except that the dental restorative hardenable compositions of each of the examples and comparative examples were vacuum degassed, filled into stainless steel molds of different sizes (dimensions: 1.2 mm x 4 mm x 14 mm), the support distance when using a universal testing machine was 12 mm, and 10 pieces of the hardened material were prepared as samples. The bending strength of the dental composite resin was judged to be good if it was 150 MPa or more, and 180 MPa or more was even better. The bending modulus of the dental composite resin was judged to be good if it was 8 GPa or more, and 10 GPa or more was even better. The bending strength of the dental mill blanks was judged to be good if it was 200 MPa or more, and 240 MPa or more was even better. The bending modulus of the dental mill blank was judged to be good if it was 12 GPa or more, and 15 GPa or more was even better. As for the mechanical strength, the blanks that met both the bending strength and bending modulus standards were judged to be acceptable.

[0133] Test Example 2 [Water resistance (three-point bending test)] Regarding the dental composite resin, samples of the hardened products of the dental restorative hardenable compositions according to the respective Examples and Comparative Examples were immersed in water at 37°C for 30 days, and then the bending strength and bending modulus were measured in the same manner as in Test Example 1 above (n=5). Regarding the dental mill blanks, measurements were performed in the same manner as for the dental composite resin, except that n=10. The test results of Test Example 1 were taken as the initial bending strength and bending modulus, and the rate of change (decrease rate) of bending strength and bending modulus after immersion in water at 37°C for 30 days was calculated by the following formula, and if the decrease rate is 10% or less, the water resistance is excellent. Decrease in bending strength due to immersion (%) = [{initial bending strength (MPa) - bending strength after immersion in water (MPa)} / initial bending strength (MPa)] x 100 Decrease in bending modulus due to immersion (%) = [{initial bending modulus (GPa) - bending modulus after immersion in water (GPa)} / initial bending modulus (GPa)] x 100

[0134] Test Example 3 [Abrasiveness] The dental restorative hardenable compositions of each of the examples and comparative examples were vacuum degassed and then filled into a Teflon (registered trademark) mold (diameter 10 mm, thickness 2.0 mm). The upper and lower surfaces were pressed with slide glass, and the composition was hardened by irradiating light only from the upper side with a dental polymerization LED light irradiator (product name "Pencure 2000", manufactured by Morita Corporation) for 10 seconds to obtain a sample (n=2). The sample was removed from the Teflon (registered trademark) mold, and the clean smooth surface was polished under dry conditions with #600 abrasive paper. Furthermore, the smooth surface was polished for 10 seconds with a silicone point brown (manufactured by Matsukaze Co., Ltd.) under water injection conditions using Volvere RX (manufactured by Nakanishi Co., Ltd.) as a technical engine, and then polished for 10 seconds with a silicone point blue (manufactured by Matsukaze Co., Ltd.) at a rotation speed of about 5000 rpm. The gloss of the resulting polished surface was measured using a gloss meter (VG 7000, manufactured by Nippon Denshoku Industries Co., Ltd.) and expressed as a percentage of the mirror, which was taken as 100%. The measurement angle was 60°. The average measured values ​​are shown in Tables 4 and 5. A gloss of 80% or more is preferable, and 85% or more is more preferable.

[0135] Test Example 4 [Paste operability (adhesive strength)] The dental restorative hardenable compositions of each of the Examples and Comparative Examples were vacuum degassed, filled into a syringe, and left at 25°C for 24 hours to be used as samples for the adhesion test. The paste was extruded from the syringe and filled into a cup having a capacity of lower bottom surface Φ11mm x upper surface Φ13mm x height 8mm. A jig having a stainless steel cylinder of Φ10mm x 5mm at the tip was attached to a small tabletop tester (Shimadzu Corporation, EZ Test), and the bottom surface of the stainless steel cylinder attached to the cylindrical jig was lightly brought into contact with the paste surface filled, and then the maximum stress when pulled up at a crosshead speed of 50mm / min was taken as the adhesion force to the stainless steel plate at 25°C (n=2). The average measured values ​​are shown in Table 4. As an evaluation of the operability of the paste, the adhesion force is preferably 1.5N or less, more preferably 1.0N or less. On the other hand, an adhesive force of 2.0 N or greater is judged to result in poor manipulability of the paste when filling with a dental instrument.

[0136] Test Example 5 [Polymerization shrinkage stress] The dental restorative hardenable composition obtained in each Example or Comparative Example was filled into a ring-shaped mold (made of stainless steel, inner diameter 5.5 mm x thickness 0.8 mm) placed on a glass plate with a thickness of 4.0 mm. The glass plate was sandblasted with alumina powder having a particle size of 50 μm. A stainless steel jig (φ5 ​​mm) connected to a universal testing machine (manufactured by Shimadzu Corporation, product name "Autograph AG-I 100kN") was placed on the filled paste, and the dental restorative hardenable composition was sandwiched between the mold. Next, the paste was irradiated with light through the glass plate for 20 seconds using a dental polymerization LED light irradiator (product name "Pencure 2000", manufactured by Morita Corporation) to harden the paste. At this time, the polymerization shrinkage stress accompanying hardening due to the polymerization reaction of the dental restorative hardenable composition, which progresses due to the light irradiation, was measured by the universal testing machine (n=3). The average values ​​of the measured values ​​are shown in Table 4. The polymerization shrinkage stress is preferably 10.0 MPa or less, more preferably 9.8 MPa or less, further preferably 9.5 MPa or less, particularly preferably 9.0 MPa or less.

[0137] Test Example 6 [Bubble generation rate of cured product] The cured products of the dental restorative hardenable compositions according to the respective Examples and Comparative Examples were evaluated for the presence or absence of bubbles inside and outside the cured products (n=10) using a tabletop microfocus X-ray CT system (Shimadzu Corporation, inspeXio SMX-90CT). In evaluating the bubble generation rate of the cured products, the number of bubbles in the cured products is preferably 1 or less, and most preferably 0. On the other hand, if there are 3 or more bubbles, the quality is judged to be poor from the viewpoints of reduced mechanical strength and poor appearance.

[0138] [Examples 1 to 16, Comparative Examples 1 to 4] (Dental composite resin) The polymerizable monomer-containing compositions (M1) to (M12), inorganic fillers (C1) to (C4), inorganic fillers (C6) and (C7), and prepolymers (P1) to (P3) obtained in the above-mentioned Production Examples were kneaded in the composition ratios shown in Table 4 below to make a homogenous mixture, which was then vacuum-defoamed to prepare paste-like dental restorative hardenable compositions of Examples 1 to 16 and Comparative Examples 1 to 4. The above-mentioned property evaluation tests (Test Examples 1 to 5) were carried out on the prepared dental restorative hardenable compositions. The results are shown in Table 4 below.

[0139] [Table 4]

[0140] As shown in Table 4, the operability of the pastes obtained in Examples 1 to 16 was all good. In addition, the cured products had high mechanical strength, and there was no decrease in strength when immersed in 37°C water, which is assumed to be in the oral cavity, and it was found to be excellent in water resistance. Furthermore, it was found that the cured products had excellent abrasiveness. In addition, the pastes obtained in Examples 12 to 16 had reduced polymerization shrinkage stress. In contrast, the paste obtained in Comparative Example 1 had low mechanical strength and water resistance. Moreover, the paste obtained in Comparative Example 2 had slightly low mechanical strength and water resistance, but was very poor in abrasiveness and operability. Furthermore, the pastes obtained in Comparative Examples 3 and 4 had very poor mechanical strength and water resistance, and Comparative Example 4 had very poor abrasiveness.

[0141] [Examples 17 to 20, Comparative Example 5] (Dental Mill Blanks) The polymerizable monomer-containing compositions (M13) and (M14) obtained in the above-mentioned manufacturing examples, and the inorganic fillers (C1) to (C5) were kneaded in the composition ratios shown in Table 5 below, and the mixture was degassed under vacuum to prepare paste-like dental restorative hardenable compositions of Examples 17 to 20 and Comparative Example 5. The dental restorative hardenable compositions were then poured into a rectangular mold measuring 20 mm x 30 mm x 60 mm, and heated at 50°C for 1 hour. Thereafter, the mixture was pressurized at 5 MPa and heated at 150°C for 1 hour to obtain a hardened product as a dental mill blank. The above-mentioned characteristic evaluation tests (Test Examples 1 to 3, 6) were carried out on the obtained hardened products. The results are shown in Table 5 below.

[0142] [Comparative Example 6] (1) 200 g of the inorganic filler (C5) obtained in the above manufacturing example was placed on the lower punch bar of a pressing die having a circular hole of φ200 mm. The powder was leveled by tapping, and the upper punch bar was placed on top and uniaxial pressing (pressing pressure: 300 kN (26.5 MPa), pressing time: 5 minutes) was performed using a table press. The upper punch bar and the lower punch bar were removed from the die, and a molded body in which the inorganic filler (C5) was aggregated was taken out. The molded body was press molded by the CIP process (pressure: 350 MPa, pressing time: 20 minutes) to obtain an inorganic filler molded body. (2) The obtained inorganic filler molded body was immersed in a polymerizable monomer-containing composition (M14), degassed under reduced pressure (10 hPa), and left to stand at 70°C for 48 hours to obtain an inorganic filler molded body impregnated with the polymerizable monomer-containing composition (polymerizable monomer-impregnated molded body). This polymerizable monomer-impregnated molded body was taken out, placed on a slide glass, and irradiated with a UV light generator (Toshiba Corporation, black light fluorescent lamp) for 60 minutes to perform photopolymerization. After that, it was heated at 70°C for 24 hours using a hot air dryer, and then heated at 110°C for 5 hours to obtain a cured product as a dental mill blank. The above-mentioned characteristic evaluation tests (Test Examples 1 to 3, 6) were carried out on the obtained cured product. The results are shown in Table 5 below.

[0143] [Table 5]

[0144] All the cured products obtained in Examples 17 to 20 were free of air bubbles. In addition, it was found that the cured products had high mechanical strength, and there was no decrease in strength when immersed in 37°C water, which simulates the oral cavity, and that the cured products had excellent water resistance. In addition, it was found that the cured products had excellent abrasive properties. In contrast, many air bubbles were found in the cured product obtained in Comparative Example 5, and the mechanical strength and water resistance were low. In addition, the cured product obtained in Comparative Example 6 also had low water resistance and low abrasive properties.

[0145] From the above results, it was found that the dental restorative hardenable composition of the present invention has high mechanical strength, excellent water resistance, and excellent abrasion resistance after curing. It was also found that the dental restorative hardenable composition of the present invention has excellent paste operability and can suppress the generation of bubbles in the cured product. [Industrial Applicability]

[0146] The dental restorative hardenable composition of the present invention has high mechanical strength, excellent water resistance and abrasiveness after curing. The dental restorative hardenable composition of the present invention has excellent paste operability, i.e., excellent handling, and has sufficient mechanical strength to be able to replace natural teeth, and is suitable for use as a material for restoring missing teeth or caries, particularly as a dental composite resin. The hardened composition is suitable for use as a dental mill blank.

Claims

1. The present invention comprises a (meth)acrylic acid ester compound (A) having two or more (meth)acryloyloxy groups in one molecule, a mono(meth)acrylic acid ester compound (B), an inorganic filler (C) having an average primary particle size of 0.01 to 5 μm, and a polymerization initiator (D), and the mono(meth)acrylic acid ester compound (B) is a mono(meth)acrylic acid ester compound (B-2) represented by the following general formula (II): 【Chemistry 1】 [In the formula, R 2 are independently a group represented by the following general formula (i) or a group represented by the following general formula (ii), and X is an oxygen atom. 【Chemistry 2】 【Chemistry 3】 (In the formula, R 3 and R 5 are each independently a divalent hydrocarbon group having 1 to 10 carbon atoms; R 4 and R 6 each independently represents a hydrogen atom or a methyl group, and k and l each independently represent an integer of 0 to 6.

1. A hardenable composition for dental restoration comprising:

2. 2. The dental restorative hardenable composition according to claim 1, wherein the content of the inorganic filler (C) is 50 to 95 mass % based on the total amount of the dental restorative hardenable composition.

3. 3. The dental restorative hardenable composition according to claim 1, wherein k and l are 0 or 1.

4. The hardenable composition for dental restoration according to any one of claims 1 to 3, wherein the (meth)acrylic acid ester compound (A) includes a compound having a cyclic structure.

5. 5. The dental restorative hardenable composition according to claim 4, wherein the compound having a cyclic structure is a compound (A-1) having an aromatic ring.

6. 6. The dental restorative hardenable composition according to claim 5, wherein the compound (A-1) having an aromatic ring is a compound having a bisphenol A skeleton.

7. The hardenable composition for dental restoration according to any one of claims 1 to 6, wherein the (meth)acrylic acid ester compound (A) comprises a compound having no hydroxy group, no carboxy group, no primary amino group, no secondary amino group, no amide group, no urea bond, and no urethane bond.

8. 8. The hardenable composition for dental restoration according to claim 1, which is substantially free of a compound having a nitrogen-containing heterocycle and a polymerizable functional group.

9. The dental restorative hardenable composition according to any one of claims 1 to 8, wherein the polymerization initiator (D) comprises a photopolymerization initiator.

10. The dental restorative hardenable composition according to any one of claims 1 to 9, wherein the polymerization initiator (D) comprises a thermal polymerization initiator.

11. The dental restorative hardenable composition according to any one of claims 1 to 10, further comprising a polymer.

12. 12. The dental restorative hardenable composition of claim 11, wherein the polymer is a prepolymer having unreacted polymerizable functional groups.

13. 13. The hardenable composition for dental restoration according to claim 12, wherein the prepolymer has 5 or more and 1,000 or less unreacted polymerizable functional groups per molecule.

14. 14. The dental restorative hardenable composition according to claim 12 or 13, wherein the prepolymer has a weight average molecular weight of 1,000 or more and 1,000,000 or less.

15. A dental composite resin comprising the dental restorative hardenable composition according to any one of claims 1 to 14.

16. A dental mill blank comprising the dental restorative hardenable composition according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Dental adhesive composition

    JP1989113478A

  • Curable composition for dental use

    JP2007126417A

  • Dental restorative material composition

    JP2016008211A

  • Dental self-curing resin cement compositions

    US20050049326A1

  • Light-curing dental composites with increasing opacity

    US20170224591A1